2017
DOI: 10.1590/s2175-97902017000300012
|View full text |Cite
|
Sign up to set email alerts
|

HPLC method development and validation for the estimation of Axitinib in rabbit plasma

Abstract: A rapid, sensitive, and accurate high performance liquid chromatography for the determination of axitinib (AN) in rabbit plasma is developed using crizotinibe as an internal standard (IS). Axitinib is a tyrosine kinase inhibitor, used in the treatment of advanced kidney cancer, which works by slowing or stopping the growth of cancer cells. The chromatographic separation was performed on a Waters 2695, Kromosil (150 mm × 4.6 mm, 5 µm) column using a mobile phase containing buffer (pH 4.6) and acetonitrile in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…The % mean recovery was higher and calculated as 98.86%, 99.015% and 100.10% respectively for 0.5μg/mL, 5μg/mL and 10μg/mL. The validation results of the analytical method are similar to the studies reported in the literature for the assessment of various medicinal components in the biological samples [ 21 23 ].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The % mean recovery was higher and calculated as 98.86%, 99.015% and 100.10% respectively for 0.5μg/mL, 5μg/mL and 10μg/mL. The validation results of the analytical method are similar to the studies reported in the literature for the assessment of various medicinal components in the biological samples [ 21 23 ].…”
Section: Resultssupporting
confidence: 82%
“…The % mean recovery was higher and calculated as 98.86%, 99.015% and 100.10% respectively for 0.5μg/mL, 5μg/mL and 10μg/mL. The validation results of the analytical method are similar to the studies reported in the literature for the assessment of various medicinal components in the biological samples [21][22][23]. The present study also estimates the significant PK parameters of the test formulation (newly developed) and the reference brand of aceclofenac (100mg) tablets.…”
Section: Plos Onesupporting
confidence: 83%
“…In a HPLC method idelalisib and ibrutinib (IS) were separated using 0.1% perchloric acid and acetonitrile as the mobile phase in 85:15 ratio at a flow rate of 1 mL/min on a reversed‐phase C18 column. The UV detection was achieved at 270 nm (Suneetha & Sharmila, ). Veeraraghavan et al () reported a simultaneous quantification of idelalisib and fludarabine for analyzing samples from a rat pharmacokinetic study using LC‐ESI‐MS/MS in the positive ionization mode as described under fludarabine.…”
Section: Case Studiesmentioning
confidence: 99%
“…In a HPLC method idelalisib and ibrutinib (IS) were separated using 0.1% perchloric acid and acetonitrile as the mobile phase in 85:15 ratio at a flow rate of 1 mL/min on a reversed-phase C18 column. The UV detection was achieved at 270 nm (Suneetha & Sharmila, 2016). Veeraraghavan et al (2014)…”
Section: Idelalisibmentioning
confidence: 99%
“…The applicability of the validated method was shown in a mice pharmacokinetic study. bit/dog/human/cancer patient plasma) are summarized in ▶ Supplementary Table 1S, [6][7][8][9][10]. In all the reported methods, the achieved recovery for idelalisib ranged between 81-92 % using either simple protein precipitation [7,8] or liquid-liquid extraction [6,9].…”
Section: Introductionmentioning
confidence: 99%